Estimating the ignition hazard of 100% cotton clothing worn by transmission and distribution line workers.
This paper describes a method of estimating the fault current magnitude necessary to ignite 100% cotton clothing worn by transmission and distribution line workers inadvertently exposed to the thermal hazards of an electric arc. This paper is intended to suggest methods for initial evaluation of the ignition hazard assessment of clothing normally worn by transmission and distribution line workers when working on overhead lines operating at 4160 volts, phase to phase, and above. Once the hazard has been identified a further risk analysis is required
Keywords: 4160 V; Cotton clothing; Distribution line workers; Electric arc; Fault current magnitude estimation; Ignition hazard assessment; Ignition hazard estimation; Overhead lines; Phase to phase; Risk analysis; Thermal hazards; Transmission line workers